The significance of Trk receptors in pancreatic cancer - Matthew D Johnson; Brandon Stone; Bryan J Thibodeau; Andrew M Baschnagel; Sandra Galoforo; Laura E Fortier; Billie Ketelsen; Samreen Ahmed; Zakiya Kelley; Alaa Hana; Thomas G Wilson; John M Robertson; et al. (Tumor Biology)
This study investigated the Trk receptor family as a therapeutic target in pancreatic ductal adenocarcinoma and assessed their prognostic significance. Global gene expression analysis was investigated in prospectively collected pancreatic ductal adenocarcinomas that had either undergone neoadjuvant chemoradiation or were treated by surgery. PANC-1 and MIA-PaCa-2 cell lines were investigated to establish whether fractionated radiation altered expression of four neuroendocrine genes and whether this resulted in subsequent changes in radiosensitivity. A specific inhibitor of TrkA, B, and C, AstraZeneca 1332, was investigated in vitro and in vivo in combination with radiation. A tissue microarray was constructed from 77 pancreatic ductal adenocarcinoma patients who had undergone neoadjuvant chemoradiation and the Trk receptor, and neurogenic differentiation 1 expression was assessed and correlated with overall survival. A total of 99 genes were identified that were differentially expressed in the chemoradiation patients with neuroendocrine genes and pathways, in particular the neurogenic differentiation 1 and Trk receptor family, being prominent. Fractionated radiation upregulated the expression of neuroendocrine genes, and AstraZeneca 1332 treatment in vitro enhanced radiosensitivity. No added effect of AstraZeneca 1332 was observed in vivo. Trk receptor expression varied between isoforms but did not correlate significantly with clinical outcome. Radiation treatment upregulated neuroendocrine gene expression but the Trk receptor family does not appear to be a promising treatment target.